Communication, How Important Is It For Advertising And Marketing Industry, (With The Special Reference To Foody Business) (International Journal of Scientific Research and Management (IJSRM), 2016)
We all are aware about the power of correct usage of words, but beside the correct usage, the appropriate selection of the words, and then communicating it in an effective manner; it’s an art and science. Now the question arise that why am I calling the communication as an art and science, the answer to this is that since it requires great rules and regulation to convince the customers and target them with the appropriate channel of communication towards the products, hence it is a science, and as its an art that how are you managing the communication, that is why we are referring the term communication as adroitness. The purpose of this research paper is to bring out that how the communication is important for both advertising and marketing world & what way and in which pattern the FOODY WORLD is using communication for its marketing and advertising dimension